The Muslim woman and her role in making generations, Lady Zainab (peace be upon him) as a model - Hamed Hadi Baden Salamlan / Khalil Hassan Rahak Al-Zarkani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The distinguished humanitarian message with morals, social etiquette and educational means elevate family upbringing for success, and this is linked to morals, and the Islamic religion considers morals the most important characteristic of man, The message of Islam is an ethical message, and the interest in building generations is linked to the general educational curriculum in building an upright personality and building a virtuous civilized generation.  The foundations of success in married life are moral principles, and ethics have a major role in changing the current reality for the better. A successful wife is the one who is able to properly raise her children, taking into account the rights of her husband, on the contrary, a mother who does not know the provisions of her religion will raise in society a generation that does not know the rights and laws of God.The woman is the mother, who preserves her family's identity by instilling high moral values; for the child to receive from its inception because if the generation goes beyond the stage of childhood and the mother neglects the moral aspect when raising it, it is difficult to direct and correct it.In addition, the woman must develop a platform to follow the generation through all its actions, without making it feel that it is being watched and the mother should be wary of what society receives through all media and social media, those media include many dangerous directives that negatively reflect on the life of the contemporary generation in the future, and cause the disintegration of the family, of which women are the main element.As a result, the bonds between the members of society are lost, and this leads to the collapse of moral foundations, and the destruction of love and tenderness among family members. Without women, there is no development in all areas of life.Generations rise through women, in addition to that, society develops and grows with the cultural and civilized nature of women, and without women, society will suffer intellectual and scientific backwardness.